Identification of Potential Tourist Attractions of Pasetran Gondo Mayit Beach in Tambakrejo Village, Wonotirto District, Blitar Regency, Indonesia - Rahayu, Desy Ratna; Purnomo, Agus (PT. Pena Produktif Kreatif, 2024)
Tourism is one aspect that significantly contributes to economic growth. This research aims to identify the potential attractions of Pasetran Gondo Mayit Beach using a quantitative approach and a cross-sectional survey design. Primary data collected include the 4A elements: attraction, accessibility, amenities, and ancillary services. Meanwhile, secondary data encompass the number of tourist visits obtained from the Tourism and Culture Office of Blitar Regency and books, theses, journals, and images related to the research. The data collection technique employed is observation, which is analyzed using quantitative descriptive methods. The identification results indicate several variations of attractions that Pasetran Gondo Mayit Beach offers, such as natural, cultural, artificial, and activity-based attractions. Accessibility to Pasetran Gondo Mayit Beach is considered sufficient. Some amenities are available in the area, such as food courts and accommodations. However, additional services, such as the availability of information boards and tour guide services, still need attention. The hope is that these identification results will provide a deeper insight into the potential attractions of Pasetran Gondo Mayit Beach, serving as a strategic guide for destination managers to increase tourist visits.